Ø§Ù„Ø¹ÙˆØ§Ù…Ù„ Ø§Ù„Ù„ØºÙˆÙŠØ© Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¤Ø³Ø³Ø§Øª ØªØ·ÙˆÙŠØ± Ø§Ù„Ù„ØºØ§Øª Ø§Ù„Ø£Ø¬Ù†Ø¨ÙŠØ© Ù…Ø¹Ù‡Ø¯ Ø§Ù„ÙŠØ§Ø³ÙŠÙ†ÙŠ Ø¨Ø§Ø³ÙˆØ±ÙˆØ§Ù† - Mahmudah, Menik (INTAJUNA : Jurnal Hasil Pemikiran, Penelitian, Produk Bidang Pendidikan Bahasa Arab, 2020)
Research objectives to find out the factors often appear in the context of improving the quality of Arabic language learning in foreign language development institutionsLPBA Yasni Basorwan Institute and how to overcome various obstacles. Qualitative research methods are used to obtain in-depth data and real data, and the tools of observational research, interview, documentation and data analysis is the process of research and compilation systematic data were obtained from interviews, field observations and other materials, so that they are easy to understand and the results can be science for others. The author's data analysis method used the Milles and Huberman model Language factors Students with basic literacy Arabic letters are very difficult for teachers so parties The school seeks to classify students into class A Basic Reading and Writing Good. Non-linguistic factors 1) teacher, 2) students, 3) method, 4) environment and 5) educational media. Keywords: Language factors, Arabic language learning, LPBA